Concomitant ALK Fusion and TP53/EGFR Mutation Lead to Adverse Prognostic Outcome - Mingyuan Du; Cuiwei Liu; Leichong Chen; Zhenyu Li; Sijia Zhang; Rui Meng (The Clinical Respiratory Journal)
ABSTRACT Lung cancer treatment has evolved at the molecular level. Detecting the presence of driver genes in lung cancer fundamentally alters the choice of therapeutic regimens and the outcome of this disease. ALK fusion mutation is one of the most important mutations in nonsmall cell lung cancer (NSCLC). Also, it often has other coexisting mutation types. TP53 is the most common coexisting mutation type, whereas the EGFR/ALK coexisting mutation type is extremely rare. There is still no definite conclusion about the impact of the multimutation and best treatment options for NSCLC patients with advanced multimutation. In this study, we report three cases of NSCLC with ALK fusion mutations as well as ALK combined with TP53 mutations and ALK combined with EGFR mutations. Combining cases from our oncology center and previous literature, we found that NSCLC patients with coexisting ALK fusion mutations and other mutations have poorer response to targeted therapy and poorer prognosis, and we also compared the efficacy rates of various types of coexisting mutations for different treatment regimens. Therefore, this review can help to evaluate the prognosis of NSCLC patients with coexisting mutations and the efficacy of targeted therapies and to find more favorable treatment options for patients with this type of coexisting mutations.